Photocatalytic degradation of dimethyl phthalate and low-density polyethylene film over Dual Zscheme Zinc Oxide/Bismuth Tungstate/Spinel Ferrite under sunlight irradiation - Chin, Ying Hui (2023)
Dimethyl phthalate (DMP) is commonly employed as a plasticizer in plastic packaging, cosmetic products and automotive spare parts. Due to high demand for plastic products and its mobility, DMP has become widespread in the environment, posing health risks to humans and negative impacts on the environment as an endocrine disruptor with carcinogenic, teratogenic and mutagenic properties. Therefore, this study aims to develop an effective approach to mitigate the negative impacts caused by DMP. Photocatalysis has received numerous attentions owe to its promising performance in degrading organic pollutants in wastewater has been selected as the primary treatment method. In this study, Brassica Oleracea-like SF20BWZ, (SF= SrFe2O4, BaFe2O4 and CaFe2O4) composites were synthesized using a hydrothermalprecipitation method. The performance of as-synthesized photocatalysts were evaluated over photodegradation of DMP and LDPE film under sunlight irradiation. The XRD results showed that the ZnO and Bi2WO6 revealed wurtzite hexagonal structure and orthorhombic structure, respectively. The existence of SF characteristic peaks in XRD spectra confirmed the successful construction of SF20BWZ composites. The FTIR analysis further confirmed the presence of ZnO, Bi2WO6 and SF in SF20BWZ composites via their relative stretching bands. The findings from FESEM and EDX analysis demonstrated the ZnO and SF distributed homogeneously on Bi2WO6 and formed Brassica Oleracea-like SF20BWZ composite. TEM analysis also confirmed the successful construction of Sr20BWZ composite through their respective lattice spacing measurement. XPS result demonstrated that Sr20BWZ composite comprised of Zn 2p, Bi 4f, O 1s, W 4f, Sr 3d and Fe 2p. VSM analysis verified the magnetic properties of 10Sr20BWZ composite. Under sunlight irradiation, 10Sr20BWZ composite exhibited the best photocatalytic performance among the as-prepared composites. 10Sr20BWZ can fully degrade the DMP (100% removal) under optimum conditions: catalyst loading = 1g/L and pH =7. The introduction of foreign substances into the system reduced the photodegradation performance. The extraordinary performance of 10Sr20BWZ composite was attributed to excellent electronhole pair separation efficiency and the lowest charge resistance. This was ratified in TPR and EIS experiments. The active species study revealed that all •OH, h+ , •O2 − and